Cryoglobulinemic HCV-related membranoproliferative glomerulonephritis with TMA - secondary HUS or infection-triggered aHUS? - Teixeira,Ana Catarina (2019)
Introduction: Membranoproliferative glomerulonephritis is a pattern of glomerular injury on renal biopsy with characteristic light microscopic changes, namely mesangial hypercellularity, endocapillary proliferation and double contour formation along the glomerular capillary walls. This pattern does not represent a disease per se but can occur as a result of different pathologic processes. Case Presentation: We present a case of a 37-year-old caucasian female patient with thrombotic microangiopathy (TMA), severe hypertension and immune-complex-mediated glomerulonephritis, secondary to hepatitis C virus (HCV) infection. Steroid therapy and fresh-frozen plasma infusions were started, with progressive improvement of lab results. Treatment of HCV infection was started with direct-acting antiviral therapy. The results of the genetic study of the complement alternative pathway regulatory proteins were positive for a homozygote variant of the gene CFHR5 (p.Val110Ala) and a homozygote deletion on CFHR3/CFHR1 proteins. Discussion: Hypertension is commonly associated with TMA and could explain the features of this case. Nevertheless, the differential diagnosis is often difficult because TMA caused by hypertension is indistinguishable from all other entities. The finding of a homozygote variant of the gene CFHR5, and a homozygote deletion on CFHR3/CFHR1 proteins, raised the possibility that this case might have been an Atypical Hemolytic Uremic Syndrome (aHUS) triggered by the endothelial damage caused by the HCV-related cryoglobulinemic glomerulonephritis